EXISTENTIALIST FEMINISM IN MOMMY ASF'S NOVEL LAYANGAN PUTUS - Eka Putradyn KJ Sitepu; Muhammad Ali Pawiro; Purwanto Siwi (Universitas Islam Sumatera Utara, 2023)
The research is concerned with women's movements portrayed in Mommy Asf’s novel Layangan Putus. It objectively finds and discusses a mother's individual movements through transcendence to upholster her existence, particularly in an attempt to overcome and improve herself even without a husband's support, as shown by Kinan, the main female character in the novel. The fact that a woman is always marginalized based on social reality, especially a woman, becomes the background of the study. The research is conducted using the descriptive-qualitative method proposed by Creswell. The theory applied in this research is the sexist feminist theory proposed by Simone de Beauvoir. The finding concerns the woman's movements described in the novel using Beauvoir's existentialist feminism. The results show that Kinan, as the main female character, can overcome and improve herself in life, as evidenced by the four transcendences of Beauvoir's theory to uphold her existence as a manifestation of Owen's movements: Kinan is able to work, become intellectual, achieve social transformation, and refuse the role of otherness